The Effect of Market Orientation, Learning Orientation and Product Innovation Agility on Fashion MSMEs Business Performance at Trunojoyo Area, Bandung City - Fajar Sidiq Adi Prabowo; Muhamad Fauzan Oktavian; Deden Syarif Hidayatullah (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2022)
The creative economy industry in the country continues to experience a significant increase, this is evidenced that Indonesia's creative economy plays an important role in gross domestic product (GDP) which is in the top three in the world after the United States with the Hollywood industry and Korea with K-Pop. Micro, small and medium enterprises or MSMEs also play a very important role in the movement and growth of the Indonesian economy. As a developing country with a very large population, the small and medium-sized business sector has helped the government in terms of employment. One part of the creative industry or sub-sector of the creative industry that is currently growing very rapidly in Indonesia is the fashion industry. The fashion industry, which is classified as a creative industry, is currently growing very quickly as part of a lifestyle in fashion. At this time, it has become a separate trend for the people of Indonesia. This study aims to determine the effect of market orientation, learning orientation, and product innovation agility as mediating variables on the business performance of MSMEs in the fashion sector in the Trunojoyo Street area, Bandung city. This study uses quantitative methods and the data collection method used in this study is the distribution of questionnaires. The sampling technique used in this study is a probability sampling technique with a saturated sample technique where the sample in this study is the entire population taken, namely all fashion MSMEs in the Trunojoyo street area, Bandung, amounting to 100 MSMEs The data analysis method used in this study is Structural Equation Modeling (SEM) with data processing carried out using SmartPLS.